Therapeutic Potential of Indian Mackerel against Carbon Tetrachloride Induced Hepatotoxicity in Rats - Harshini, V Sri; Srividya, G; Kumar, P Ravi; Swaroop, M Naveen; Samatha, V; Anjaneyulu, P; G Sai; Kour, S Simran (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was designed with an attempt to explore the therapeutic potential of Indian mackerel against carbon tetrachloride (CCl4) induced hepatic damage in rats. Male Wistar albino rats, weighing about 150–200 g, were randomly assigned to 3 groups of sixeach. Rats in Group I (control) received 1% DMSO orally for 3 weeks and olive oil I/P twice a week in the 2nd and 3rd week. Group II and III received CCl4@ 1ml/kg B.wt in olive oil (1:1) I/P twice a week in 2nd and 3rd week. Whereas Group III rats were administered with fish extract @ 300mg/Kg B.wt orally for 3 weeks daily. The extent of CCl4 induced damage was measured by estimating ALT, AST, ALP, bilirubin in serum, total protein and albumin in plasma, SOD, CAT, GSH, GPx and TBARS in liver tissue homogenate and histopathological examination of liver. CCl4 induced oxidative damage was evidenced by elevated levels of ALT, AST, ALP, TBARS and reduced levels of GSH, SOD, CAT, GPX and total protein. Treatment with fish extract along with CCl4 led to reversal in the altered hepatic biomarkers and a significant reduction in the MDA levels, improvement in antioxidant markers when compared to CCl4 induced hepatotoxic group. Thus, results of the present study indicated that fish extract offered protection against CCl4-induced hepatic damage in rats due to its antioxidant effect.